PENINGKATAN KEMAMPUAN MEMBACA NYARING MENGGUNAKAN MEDIA CERITA BERGAMBAR PADA MATA PELAJARAN BAHASA INDONESIA DIKELAS I SD NEGERI 104245 TUMPATAN TAHUN AJARAN 2018-2019 - Dewi Suyani; Wiwik Lestari (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2020)
This study aims to enhance first-grade students' oral reading skills through illustrated story media. Action Research (AR) was conducted at SD Negeri 104245 Tumpatan from August to October 2019, involving 30 students as participants. It consisted of two cycles with four stages each: planning, implementation, observation, and reflection. Initial observations revealed that students faced difficulties in reading fluently and lacked proficiency in oral reading techniques such as pronunciation, intonation, punctuation, and pauses. Illustrated story media was employed to address these issues, proving effective in improving student motivation and reading skills. The average student scores increased from 66.3 with a Minimum Mastery Criteria (KKM) achievement of 47% in the pre-action phase to 70.5 with a 70% KKM achievement after Cycle I, and 73 with a 96% KKM achievement after Cycle II. These improvements demonstrate the effectiveness of illustrated story media in education. Teachers are encouraged to integrate this method according to their teaching materials.